PATIENT VOICES AND PRACTICE ACCREDITATION: A NATURAL EXPERIMENT IN PRIMARY CARE QUALITY ASSESSMENT - Dr Rachit Srivastava; Dr. N. Anoop; Ajay M; D. Jothieswari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Many general practices use accreditation to maintain high patient safety and quality of care. Yet, we don’t know much about the effects of these services on what patients think of healthcare quality. One of the goals of this study was to discover if accreditation improves the quality of care as seen by patients. Researchers took advantage of the sequential introduction of a national accreditation programme in a natural cluster randomised design. Responses to the same validated questionnaire were collected from both accredited and non-accredited practices. Multilevel regression was used to study differences between various key domains. No meaningful differences in patient-reported outcomes such as communication, accessibility and satisfaction, were observed between patients treated at accredited and non-accredited practices. The presence of accreditation did not make much difference in patient-rated quality of care. Any future accreditation process needs to focus on patient care and help practices apply improvements to their patient care.